Get expert advice and community support for your questions on IDNLearn.com. Get comprehensive and trustworthy answers to all your questions from our knowledgeable community members.

Drag the tiles to the boxes to form correct pairs.

Let [tex]u = \langle -5, 2 \rangle[/tex], [tex]v = \langle -1, -3 \rangle[/tex], and [tex]w = \langle 3, -4 \rangle[/tex]. Find the resultant of each statement.

Tiles:
- [tex]\langle -22, 20 \rangle[/tex]
- [tex]\langle 2, -3 \rangle[/tex]
- [tex]\langle 9, -7 \rangle[/tex]
- [tex]\langle -12, 3 \rangle[/tex]

Pairs:
1. [tex]-2u + v[/tex]
2. [tex]3v - 3w[/tex]
3. [tex]u - v + 2w[/tex]
4. [tex]2u - 4w[/tex]

[tex]\longleftrightarrow[/tex]


Sagot :

Alright, let's find the resultant of each statement step-by-step. Given the vectors [tex]\( u = \langle -5, 2 \rangle \)[/tex], [tex]\( v = \langle -1, -3 \rangle \)[/tex], and [tex]\( w = \langle 3, -4 \rangle \)[/tex], we need to find the result of each pair operation and match them with the correct tiles.

1. Pair: [tex]\( -2u + v \)[/tex]

Calculating this:
[tex]\[ -2u = -2 \cdot \langle -5, 2 \rangle = \langle 10, -4 \rangle \][/tex]
[tex]\[ -2u + v = \langle 10, -4 \rangle + \langle -1, -3 \rangle = \langle 10 - 1, -4 - 3 \rangle = \langle 9, -7 \rangle \][/tex]

So, the result of [tex]\( -2u + v \)[/tex] is [tex]\( \langle 9, -7 \rangle \)[/tex].

2. Pair: [tex]\( 3v - 3w \)[/tex]

Calculating this:
[tex]\[ 3v = 3 \cdot \langle -1, -3 \rangle = \langle -3, -9 \rangle \][/tex]
[tex]\[ 3w = 3 \cdot \langle 3, -4 \rangle = \langle 9, -12 \rangle \][/tex]
[tex]\[ 3v - 3w = \langle -3, -9 \rangle - \langle 9, -12 \rangle = \langle -3 - 9, -9 + 12 \rangle = \langle -12, 3 \rangle \][/tex]

So, the result of [tex]\( 3v - 3w \)[/tex] is [tex]\( \langle -12, 3 \rangle \)[/tex].

3. Pair: [tex]\( u - v + 2w \)[/tex]

Calculating this:
[tex]\[ -v = -1 \cdot \langle -1, -3 \rangle = \langle 1, 3 \rangle \][/tex]
[tex]\[ 2w = 2 \cdot \langle 3, -4 \rangle = \langle 6, -8 \rangle \][/tex]
[tex]\[ u - v + 2w = \langle -5, 2 \rangle + \langle 1, 3 \rangle + \langle 6, -8 \rangle = \langle -5 + 1 + 6, 2 + 3 - 8 \rangle = \langle 2, -3 \rangle \][/tex]

So, the result of [tex]\( u - v + 2w \)[/tex] is [tex]\( \langle 2, -3 \rangle \)[/tex].

4. Pair: [tex]\( 2u - 4w \)[/tex]

Calculating this:
[tex]\[ 2u = 2 \cdot \langle -5, 2 \rangle = \langle -10, 4 \rangle \][/tex]
[tex]\[ 4w = 4 \cdot \langle 3, -4 \rangle = \langle 12, -16 \rangle \][/tex]
[tex]\[ 2u - 4w = \langle -10, 4 \rangle - \langle 12, -16 \rangle = \langle -10 - 12, 4 + 16 \rangle = \langle -22, 20 \rangle \][/tex]

So, the result of [tex]\( 2u - 4w \)[/tex] is [tex]\( \langle -22, 20 \rangle \)[/tex].

Therefore, the correct result pairs are:

- [tex]\( -2u + v \rightarrow \langle 9, -7 \rangle \)[/tex]
- [tex]\( 3v - 3w \rightarrow \langle -12, 3 \rangle \)[/tex]
- [tex]\( u - v + 2w \rightarrow \langle 2, -3 \rangle \)[/tex]
- [tex]\( 2u - 4w \rightarrow \langle -22, 20 \rangle \)[/tex]